Domestic violence and the Maria da Penha law - SOMENZARI, Nathalia Falasz (Faculdade de Filosofia e Ciências, 2017)
The main objective of this study is to demonstrate how women victims of domestic violence behave and feel when inserted in a victimization process, as well as to explain the concept of blame for women who suffer violence. It will be demonstrated that victimization and blame contribute not only to the impunity of perpetrators, but also to a low number of complaints regarding offenses related to such women. From this angle, some important points of the Maria da Penha Law (nº 11.430 / 2006) and their respective problems will be highlighted. Submissão: 2017-05-22 Aceite: 2017-08-17